2021
DOI: 10.1038/s41598-021-85108-6
|View full text |Cite
|
Sign up to set email alerts
|

A Chinese multicenter retrospective study of isolated increased nuchal translucency associated chromosome anomaly and prenatal diagnostic suggestions

Abstract: Extensive researches involving fetuses with multiple ultrasound anomalies have been conducted over the years, but only few were focused on the isolated increased nuchal translucency (NT). On top of that, these limited number of researches were all designed as single-arm studies and the control group was missing. In this study, we conducted a multicenter, retrospective study using amniotic fluid samples collected from 1197 pregnant women having fetuses with isolated increased NT (INT group) or normal NT values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…The positive rate was lower than previous reports because the NT cut-off for invasive testing in our department is 2.5 mm vs. 3.0-3.5 mm in most previous studies. Consist with these studies, aneuploidy and gross deletion/duplication accounted for more than 80% chromosomal abnormalities (NT cut-off 2.5 ~ 3.0 mm: 80% ~ 90%, NT cut-off 3.5 mm: > 90%) [16][17][18][19][20][21]. CMA could detect 1.9% more CNVs than karyotyping in serum screening group, which is consistent with previous reports [22,23].…”
Section: Discussionsupporting
confidence: 89%
“…The positive rate was lower than previous reports because the NT cut-off for invasive testing in our department is 2.5 mm vs. 3.0-3.5 mm in most previous studies. Consist with these studies, aneuploidy and gross deletion/duplication accounted for more than 80% chromosomal abnormalities (NT cut-off 2.5 ~ 3.0 mm: 80% ~ 90%, NT cut-off 3.5 mm: > 90%) [16][17][18][19][20][21]. CMA could detect 1.9% more CNVs than karyotyping in serum screening group, which is consistent with previous reports [22,23].…”
Section: Discussionsupporting
confidence: 89%
“…Karl Oliver Kagan et al demonstrated that the prevalence of abnormal karyotype was 19.2% and the trisomy 21 (68.34%) was the most common chromosome anomaly, followed by trisomy 18 (21.11%) and trisomy 13 (10.55%) [17,18]. Jin Hua et al also reported recently that the incidence of chromosome abnormality was 28.7% in increased NT group while only 7.81% was found in normal group [19]. In our study, 19.51% chromosomal abnormalities were detected by karyotype, and trisomy 21 (60.00%) was the most common, followed by trisomy 18 (12.50%), and trisomy 13 (5.00%), which was consistent with the above literature reports.…”
Section: Discussionmentioning
confidence: 99%
“…NT is the thickness of fluid collection in the fetal neck, which can be observed by an ultrasound scan between 11 and 13 + 6 weeks of gestation. Increased NT has been reported to be associated with chromosomal abnormalities and fetal structural defects [ 5 , 6 ]. CH can be clearly differentiated from a simple increase in NT.…”
Section: Discussionmentioning
confidence: 99%